Band gap and conductivity evaluation of carbon nanotube with hematite for green ammonia synthesis - Rehman, Z.U. (American Institute of Physics Inc., 2016)
To understand the change in number of electrons, band gap and total energy in the catalyst simulation was performed using Cambridge Serial Total Energy Package (CASTEP). Two catalyst were taken into consideration namely carbon nanotubes (CNTs) and hematite adjacent with CNTs. The simulation based study of the adsorption of hydrogen and nitrogen with reference to change in number of electron and band-gap of carbon nano tubes and hematite mixed with carbon nanotubes was not reported in literature. For this reason carbon nanotubes band gap for different chirality and number of walls was calculated through simulation. After that simulation for number of electrons, band gap and average total energy of CNTs alone and a mixture hematite with CNTs was performed before and after adsorption of hydrogen and nitrogen. From simulation the number of electrons were found to be doubled for hematite mixed with CNTs and average total energy was also increased as compared to similar parameter for CNTs without hematite. In conclusion the hematite with carbon nanotubes is preferred candidate for ammonia synthesis using magnetic induction method. Ammonia synthesis was done using MIM. Ammonia yield was quantified by Kjaldal method. Â© 2016 Author(s).